Rethinking competency gap of prospective English teachers in Indonesia - Kurniadiansyah, Meytha Dwi; Agustina, Eliasanti; Setiawan, Rahmat (Universitas Negeri Semarang, 2025)
The teacher education system in Indonesia faces significant challenges in producing professional and competent educators. Despite a structured curriculum and professional development programs, a gap persists between graduates’ competencies and job market expectations. This study aims to assess English Education students’ readiness to meet teaching standards and examines disparities between institutional goals and graduates’ actual capabilities. Using a mixed-method sequential explanatory design, data were collected via a Likert-scale survey of 66 final-year students and in-depth interviews with principals, senior teachers, and students. The findings reveal that only 39.4% of students feel confident in speaking English, and 50% consider themselves capable of managing classrooms, although 81.9% demonstrated strong competencies in using technology. These competency gaps highlight the need for improved practical experiences, such as higher-quality and longer internship programs. Furthermore, the curriculum should prioritize speaking skills, cross-cultural understanding, and innovative pedagogical strategies to prepare teachers who are creative, adaptable, and ready to face the challenges of modern education. This study underscores the importance of strengthening collaboration between universities and educational institutions to shape professional educators capable of advancing national education quality.